8 Genuine illness and injury during europe's largest emergency service major incident exercise. (21st May 2017) - Cannon, E; Edwards, T; Fothergill, R
Abstract : Aim: Previous studies of patient presentation rates at mass gatherings have been limited to social events. None have assessed presentation rates in the context of a large-scale emergency service exercise where individuals (actors playing hypothetical casualties) are exposed to an environment containing many potential hazards. Methods: Exercise Unified Response was the largest multi-agency exercise ever held in Europe. It was a four-day major incident exercise in the UK, in which 2700 individuals acted as casualties. Clinical records completed by healthcare professionals providing on-site medical cover for the duration of the event were reviewed. Clinical records were included where the individual's role in the exercise was listed as 'actor'. Results: Thirty actors required medical attention, giving a patient presentation rate (PPR) of 11.1 per one thousand actors. Of these, 10% were conveyed to hospital with musculoskeletal (n=2) or head injuries (n=1); an ambulance transfer rate (ATR) of 1.11 per 1000. Just under half of all patients (40%, n=12) had a contributory factor to seeking medical help, where they had: not eaten on the day (n=4); a pre-existing condition exacerbated by the exercise, such asthma (n=3); pre-existing symptoms of acute illness (n=3), or a pre-existing injury (n=2). Conclusion: Patient presentation rate was in line with previous research1. However, we believe this is the first study to report similar data for a mass emergency service exercise. Our findings regarding the factors and pre-existing illnesses/conditions that contributed to individuals seeking medical help will be valuable in planning future large-scale exercises. Reference: Alguthami, A., Pines, J., 2014. A systematic review of noncommunicable health issues in mass gatherings. Prehosp Disaster Med, 29(2), 167–75. Conflict of interest: None declared. Funding: None declared.